2015
DOI: 10.1186/s13002-015-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal plants used for digestive system disorders by the Karen of northern Thailand

Abstract: BackgroundDigestive system disorders have a substantial effect on worldwide morbidity and mortality rates, including in Thailand, where the majority of the rural areas have a lack of proper sanitation and awareness about disease prevention. This has led to the prevalence of different types of digestive diseases. Karen people in Thailand still use medicinal plants as first aid remedies in treating these diseases. Therefore, this study aimed at documenting the plants used to cure and prevent different types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 80 publications
3
74
1
17
Order By: Relevance
“…15). Upon thorough review we found most similarity (22.78%) with Khan and Ahmad (2015) The analytical approach (Sorensen's similarity) also showed some interesting results through comparison with previous documentation on similar health care remedies (Digestive disorders) from different regions of the world like Lorestan, Iran (Delfan et al, 2015), Northern Thailand (Tangjitman et al, 2015), Eastern Cape, South Africa (Olajuyigbe and Afolayan, 2013), Kaduna State, Nigeria (Mathias et al, 2013) reveals 0% similarity with the study area. Less similarities were seen in comparison with analyzed studies that might be possibly the outcome of a momentous cultural adaption that is the main indicative of current extensive change in habitat structure and population (Leonti et al, 2009) as similarity indices are very sensitive to variation in population sizes (Wolda, 1981).…”
Section: Sorensen's Similarity Index (Si)mentioning
confidence: 65%
See 2 more Smart Citations
“…15). Upon thorough review we found most similarity (22.78%) with Khan and Ahmad (2015) The analytical approach (Sorensen's similarity) also showed some interesting results through comparison with previous documentation on similar health care remedies (Digestive disorders) from different regions of the world like Lorestan, Iran (Delfan et al, 2015), Northern Thailand (Tangjitman et al, 2015), Eastern Cape, South Africa (Olajuyigbe and Afolayan, 2013), Kaduna State, Nigeria (Mathias et al, 2013) reveals 0% similarity with the study area. Less similarities were seen in comparison with analyzed studies that might be possibly the outcome of a momentous cultural adaption that is the main indicative of current extensive change in habitat structure and population (Leonti et al, 2009) as similarity indices are very sensitive to variation in population sizes (Wolda, 1981).…”
Section: Sorensen's Similarity Index (Si)mentioning
confidence: 65%
“…Lowest F IC value was found in appetite (0.71). Many researchers reported constipation, stomach ache, diarrhea and anthelmintic as the most cited disease categories (Abbasi et al, 2013;Rokaya et al, 2014;Tangjitman et al, 2015) and gastritis by Dogan and Ugulu, (2013). As for as disease categories concerned, gastrointestinal disorders have been cited with highest F IC values in previously published study like D.I.…”
Section: Informant Consensus Factor (F Ic )mentioning
confidence: 95%
See 1 more Smart Citation
“…Ginger (Zingiber officinale Roscoe), belongs to family Zingiberaceae is one of the most important plant with various nutritional and ethnomedical values 56 . It is widely used around the world in foods as a spice and flavoring agent 57 .…”
Section: Shunthi (Zingiber Officinale Roscoe)mentioning
confidence: 99%
“…According to Tangjitman et al (2015), the leaves are part of the plant used the most widely used as a traditional medicine in comparison with other parts. Many studies have been conducted in various regions also showed the dominance of leaf organs in the use of drugs.…”
Section: Level Of Knowledge Of Tompu Society About Medicinal Plantsmentioning
confidence: 99%